High-wear-resistance tungsten steel alloy and preparation method thereof

By introducing WC, Al-Sn-B nanooxides and SiN/GO toughening equally, forming a gradient structure and adding V, Mn and Mo, the problem of insufficient wear resistance of tungsten steel alloy under extreme wear conditions is solved, and the balance between hardness, wear resistance and toughness is achieved, and the material's wear resistance and high-temperature oxidation resistance is significantly improved.

CN119571165AActive Publication Date: 2025-03-07ZHUZHOU KUNRUI CARBIDE CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411768994.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing tungsten steel alloys lack wear resistance under extreme wear conditions, and it is difficult to achieve a balance between hardness and toughness during the preparation process, which affects its overall wear resistance.

Method used

High wear-resistant tungsten steel alloys were prepared by WC, Al-Sn-B nanooxides and SiN/GO toughening equal design to form a gradient structure, the surface layer has hardness and wear resistance, the inner layer has good toughness, and the hardness and wear resistance are improved by the addition of V, Mn and Mo.

Benefits of technology

The wear resistance and high-temperature oxidation resistance of tungsten steel alloys are significantly improved, and a good balance between hardness, wear resistance, toughness and bending resistance is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571165A_ABST
    Figure CN119571165A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of hard alloys, and particularly relates to a high-wear-resistance tungsten steel alloy and a preparation method thereof. The raw materials of the high-wear-resistance tungsten steel alloy comprise WC, Al-Sn-B nanometer oxide and a SiN / GO toughening phase, the tungsten steel alloy is designed to be of a gradient structure, the surface layer has hardness and wear resistance, the inner layer has good fracture toughness, WC is the main hard phase in the tungsten steel alloy, extremely high hardness and wear resistance are provided, and the high-wear-resistance tungsten steel alloy can be used for manufacturing the high-wear-resistance tungsten steel alloy. The Al-Sn-B nano oxide is added to form a sintering aid, so that the diffusion mass transfer process of WC in high-temperature solid-phase sintering is enhanced, the densification of the tungsten steel alloy is accelerated, and the fracture toughness of the tungsten steel alloy is improved by adding the SiN / GO toughening phase and utilizing a graphene toughening mechanism; the prepared high-wear-resistance tungsten steel alloy has excellent wear resistance and high-temperature oxidation resistance, and good toughness, strength and bending resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cemented carbide, and in particular relates to a high wear-resistant tungsten steel alloy and a preparation method thereof. Background Art

[0002] Tungsten carbide-cobalt (WC-Co) cemented carbide has good comprehensive mechanical properties and is widely used in the production of cutting tools, precision molds, wear-resistant parts and other products. However, with the complexity and extremeness of the mechanical processing industry environment, its poor corrosion resistance and low high-temperature hardness are gradually exposed. Among them, the priority corrosion, softening and wear of the bonding phase are the main reasons for the reduction of product working accuracy and shortened service life. In addition, metal Co resources are relatively scarce. Compared with traditional WC-Co cemented carbide, WC cemented carbide without bonding phase has excellent wear resistance, oxidation resistance, corrosion resistance and polishing performance. Therefore, the research and development of tungsten carbide without bonding phase has become one of the hot topics in the field of cemented carbide.

[0003] Although existing tungsten steel alloys perform well in many industrial applications, their wear resistance is still insufficient under some extreme wear conditions, such as high-speed cutting and high-load grinding, resulting in a short service life. In addition, the balance between hardness and toughness of existing tungsten steel alloys is often difficult to achieve during the preparation process. Increasing the hardness often leads to a decrease in toughness, and vice versa. In the existing preparation methods, the microstructure uniformity of the alloy is poor, which affects its overall wear resistance. Therefore, there is an urgent need to develop a highly wear-resistant tungsten steel alloy that can significantly improve wear resistance while maintaining a high hardness, while optimizing the balance between hardness and toughness. Summary of the invention

[0004] In view of the deficiencies of the prior art, the present invention proposes a high wear-resistant tungsten steel alloy and a preparation method thereof. The present invention adopts WC, Al-Sn-B nano-oxide and SiN / GO toughening phase to design and prepare a high wear-resistant tungsten steel alloy, and designs the tungsten steel alloy into a gradient structure, the surface layer has hardness and wear resistance, and the internal layer has good toughness. WC is the main hard phase in the tungsten steel alloy, providing extremely high hardness and wear resistance. The addition of TiC further improves the wear resistance. The addition of Al-Sn-B nano-oxide can form a liquid-phase sintering aid, enhance the diffusion and mass transfer process of the composite material in high-temperature solid-phase sintering, thereby accelerating densification; the addition of SiN / GO toughening phase utilizes the graphene toughening mechanism to improve the toughness of the tungsten steel alloy, and the addition of V, Mn and Mo improves the hardness and wear resistance of the tungsten steel alloy, so that the high wear-resistant tungsten steel alloy prepared by the present invention has excellent wear resistance and high-temperature oxidation resistance, good toughness, strength and bending resistance.

[0005] In order to achieve the above technical objectives, the technical solutions adopted by the present invention are as follows:

[0006] The invention provides a high wear-resistant tungsten steel alloy, which is composed of the following raw materials in parts by weight: 86-92 parts of WC, 1-2.5 parts of TiC, 1-5 parts of Al-B-Sn nano-oxide, 0.5-1.2 parts of V, 1.2-2 parts of Mn, 0.2-1 parts of Mo, 0.5-1.5 parts of inhibitor, 0.1-1 parts of molding agent, and 1-3 parts of SiN / GO (silicon nitride / graphene oxide) toughening phase;

[0007] Preferably, the inhibitor is prepared by mixing VC and Cr3C2, and the mass ratio of the two is 1:0.6;

[0008] Preferably, the molding agent is polyvinyl alcohol;

[0009] The raw materials for preparing the Al-B-Sn nano-oxide are: Al(NO3)3·9H2O, acetylacetone, SnO2 and H3BO3;

[0010] The preparation method of the Al-B-Sn nano-oxide specifically comprises the following steps:

[0011] (1) Weigh Al(NO3)3·9H2O and dissolve it in ethylene glycol, add acetylacetone, stir at 60°C for 2 h, add SnO2, stir and mix to form a mixed solution;

[0012] (2) adding H3BO3 to the mixed solution obtained in step (1), stirring at a constant temperature for 1 h, to obtain a precursor mixed solution;

[0013] (3) The precursor mixed solution was aged for 48 hours to obtain a sol, and then the sol was placed in a muffle furnace for calcination. At room temperature, it was heated from room temperature to 300°C at 3°C / min, and kept warm for 2 hours, and cooled to room temperature to obtain Al-B-Sn nano-oxide.

[0014] Furthermore, the usage ratio of Al(NO3)3·9H2O, SnO2, acetylacetone and ethylene glycol is 1-2g:0.5g:5mL:30mL.

[0015] Furthermore, the dosage ratio of H3BO3 to the mixed solution is 0.1-0.3g:30mL.

[0016] The raw materials for preparing the SiN / GO toughening phase are: graphite powder, sodium nitrate and potassium permanganate;

[0017] The SiN / GO toughening phase preparation method specifically comprises the following steps:

[0018] (a) Add concentrated sulfuric acid to a beaker, slowly add graphite powder, sodium nitrate and potassium permanganate, place in a water bath at 15°C for 3 hours, and then stir at 35°C for 60 minutes using a thermostatic stirrer to form a mixed solution;

[0019] (b) adding 30% hydrogen peroxide to the mixed solution obtained in step (a), with the volume ratio of hydrogen peroxide to the mixed solution being 1:3, reacting until no bubbles are generated in the beaker, stirring at a constant speed for 60 min at room temperature, washing with deionized water 3-5 times, diluting with 0.01 M dilute hydrochloric acid to a pH value of 7, and drying in a vacuum drying oven at 75° C. for 12 h to obtain GO brown powder;

[0020] (c) dissolving the GO brown powder prepared in step (b) in a THF (tetrahydrofuran) solution, adding SiN, stirring evenly, calcining, heating to 400-600° C. at 12° C. / min at room temperature, and maintaining at 400-600° C. for 2-4 h to form a SiN / GO toughening phase;

[0021] Furthermore, the usage ratio of the graphite powder, sodium nitrate, potassium permanganate and concentrated sulfuric acid is 1g:0.6g:3g:25mL.

[0022] Furthermore, the usage ratio of the SiN and GO brown powders to THF is 0.5-1 g: 1 g: 15 mL.

[0023] The present invention also provides a method for preparing a high wear-resistant tungsten steel alloy, which specifically comprises the following steps:

[0024] S1, weighing 10-20 parts of anhydrous ethanol, adding SiN / GO toughening phase, V and Mo by weight into the anhydrous ethanol and mixing evenly to obtain a mixture, placing the mixture into a wet mill for ball milling for 24 hours, and passing through a 400-500 mesh sieve to obtain a toughening slurry;

[0025] S2, drying the toughening slurry obtained in step S1, pressing and molding to obtain a compact, placing the compact in a high vacuum tube furnace for vacuum sintering, raising the sintering temperature from room temperature to 900-1100° C. in a nitrogen atmosphere, and maintaining the temperature at 900-1100° C. for 0.5-1 h to obtain a toughening layer;

[0026] S3, weighing 80-100 parts of acetone, adding WC, TiC, Al-B-Sn nano-oxide, Mn and inhibitor into the acetone according to weight parts to form a mixed slurry, adding a molding agent according to weight parts into the mixed slurry, ball milling, and drying to obtain a powder;

[0027] S4, covering the toughening layer obtained in step S2 with the powder obtained in step S3, pressing into shape, and vacuum sintering. In a nitrogen atmosphere, rapidly raising the temperature from room temperature to 1200°C at a heating rate of 20°C / min, maintaining at 1200°C for 0.5-1h, then raising the temperature from 1200°C to 1400°C at a heating rate of 10°C / min, maintaining at 1400°C for 0.5-1h, and obtaining a high wear-resistant tungsten steel alloy after cooling.

[0028] Furthermore, the model of the wet mill is 750×1060, and the model of the vacuum tube furnace is MXG1750-60.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The invention adopts WC, Al-Sn-B nano-oxide and SiN / GO toughening phase to design and prepare high wear-resistant tungsten steel alloy. The tungsten steel alloy is designed into a gradient structure, the surface layer has hardness and wear resistance, the inner layer has good toughness, WC is the main hard phase of the tungsten steel alloy, and provides extremely high hardness and wear resistance. The addition of TiC further improves the wear resistance. The addition of Al-Sn-B nano-oxide can form a liquid-phase sintering aid, and enhance the diffusion and mass transfer process of the tungsten steel alloy in high-temperature solid-phase sintering, thereby accelerating densification; the SiN / GO toughening phase utilizes the graphene toughening mechanism to improve the fracture toughness of the tungsten steel alloy, V, Mn and Mo improve the hardness and wear resistance of the tungsten steel alloy, the addition of Mn improves the bending strength of the tungsten steel alloy, so that the tungsten steel alloy is not easy to break, and the addition of V improves the oxidation resistance of the tungsten steel alloy at high temperatures, so that the tungsten steel alloy can work normally at high temperatures. Al-Sn-B nano-oxide and WC together increase the hardness of tungsten steel alloy, because nano-particles can be used as hard phase reinforcement materials to improve the wear resistance of the alloy and increase the density of tungsten steel alloy. The high hardness and small size of Al-Sn-B nano-oxide can reduce the plowing and cutting during the wear process, thereby improving the wear resistance of tungsten steel alloy. Al-Sn-B nano-oxide can form a protective oxide film at high temperature, which helps to prevent further oxidation of tungsten steel alloy in high temperature environment. Al-Sn-B nano-oxide can enhance the corrosion resistance of tungsten steel alloy, refine the grains of tungsten steel alloy, thereby optimizing its microstructure, so that the prepared high wear-resistant tungsten steel alloy has ultrafine grain size. Al-Sn-B nano-oxide can be used as a sintering aid to promote the sintering process of other components in tungsten steel alloy, reduce the sintering temperature, shorten the sintering time, and improve the density and integrity of the material. GO has extremely high strength and excellent fracture toughness. Its two-dimensional layered structure can effectively hinder the expansion of cracks in tungsten steel alloy, thereby significantly improving the toughness of tungsten steel alloy. The addition of GO can improve the tensile strength, compressive strength and bending strength of tungsten steel alloy, so that the alloy can show better overall performance when subjected to mechanical load. The addition of Al-Sn-B nano-oxide helps to reduce cracks and holes in tungsten steel alloy. GO further reduces the fatigue crack expansion of tungsten steel alloy under cyclic load and improves its fatigue life. SiN has high thermal stability and good high-temperature mechanical properties. After compounding with GO, it can maintain the structural integrity and toughness of tungsten steel alloy under high temperature environment. SiN can form a dense oxide film at high temperature to protect the underlying material from further oxidation. The compound with GO further improves the oxidation resistance of the alloy. The oxide film formed by Al-Sn-B nano-oxide has good stability at high temperature. SiN itself has excellent wear resistance. After compounding with GO, it can further improve the wear resistance of tungsten steel alloy while maintaining toughness.Using VC and Cr3C2 as inhibitors can not only inhibit the grain growth of WC and maintain a uniform and fine grain size, but also the VC phase can increase the wear resistance of the tungsten steel alloy. The added V can also generate the VC phase at high temperature to enhance the wear resistance of the alloy. The high wear-resistant tungsten steel alloy prepared by the present invention has excellent wear resistance and high temperature oxidation resistance, good toughness, strength and bending resistance, high hardness, high density, fine and uniform structure, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a fracture morphology diagram of the high wear-resistant tungsten steel alloy prepared by the present invention;

[0032] Figure 2 A schematic diagram of the average grain size of the high wear-resistant tungsten steel alloy prepared in the present invention;

[0033] Figure 3 Schematic diagram of wear weight loss of the high wear-resistant tungsten steel alloy prepared in the present invention. DETAILED DESCRIPTION

[0034] In order to make the technical solution of the present invention better understood by the technical personnel in the field, and to make the above-mentioned features, purposes and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with the embodiments. The embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0035] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.

[0036] Embodiment 1: This embodiment provides a high wear-resistant tungsten steel alloy, which is composed of the following raw materials in parts by weight: 86 parts of WC, 1 part of TiC, 5 parts of Al-B-Sn nano-oxide, 0.5 parts of V, 1.2 parts of Mn, 0.2 parts of Mo, 0.5 parts of inhibitor, 4 parts of forming agent, and 1 part of SiN / GO toughening phase;

[0037] The inhibitor is prepared by mixing VC and Cr3C2, with a mass ratio of 1:0.6;

[0038] The molding agent is polyvinyl alcohol;

[0039] The raw materials for preparing the Al-B-Sn nano-oxide are: Al(NO3)3·9H2O, acetylacetone, SnO2 and H3BO3;

[0040] The preparation method of the Al-B-Sn nano-oxide specifically comprises the following steps:

[0041] (1) Weigh Al(NO3)3·9H2O and dissolve it in ethylene glycol, add acetylacetone, stir at a constant temperature of 60°C for 2 h, add SnO2, the amount ratio of Al(NO3)3·9H2O, SnO2, acetylacetone and ethylene glycol is 1 g:0.5 g:5 mL:30 mL, stir and mix to form a mixed solution;

[0042] (2) adding H3BO3 to the mixed solution obtained in step (1), the amount ratio of H3BO3 to the mixed solution being 0.1 g:30 mL, and stirring at a constant temperature for 1 h to obtain a precursor mixed solution;

[0043] (3) The precursor mixed solution was aged for 48 hours to obtain a sol, and then the sol was placed in a muffle furnace for calcination. At room temperature, it was heated from room temperature to 300°C at 3°C / min, and maintained at 300°C for 2 hours. It was cooled to room temperature to obtain Al-B-Sn nano-oxide.

[0044] The raw materials for preparing the SiN / GO toughening phase are: graphite powder, sodium nitrate and potassium permanganate;

[0045] The preparation method of the SiN / GO toughening phase specifically comprises the following steps:

[0046] (a) Add concentrated sulfuric acid to a beaker, slowly add graphite powder, sodium nitrate and potassium permanganate, the amount ratio of graphite powder, sodium nitrate, potassium permanganate and concentrated sulfuric acid is 1g:0.6g:3g:25mL, put it in a water bath at a temperature of 15°C for 3 hours, then stir it at a speed of 300 rpm at 35°C for 60 minutes with a thermostatic stirrer to form a mixed solution;

[0047] (b) adding 30% hydrogen peroxide to the mixed solution obtained in step (a) in a volume ratio of 1:3, reacting until no bubbles are generated in the beaker, stirring at 200 rpm for 60 min at room temperature, washing with deionized water 5 times, and then diluting and washing with 0.01 M dilute hydrochloric acid to a pH value of 7, and drying in a vacuum drying oven at 75° C. for 12 h to obtain GO brown powder;

[0048] (c) The GO brown powder prepared in step (b) was dissolved in THF, and SiN was added, with the amount ratio of SiN, GO brown powder and THF being 0.5 g:1 g:15 mL. The mixture was stirred evenly at a speed of 180 rpm and calcined, i.e., heated to 400°C at a rate of 12°C / min at room temperature and maintained at 400°C for 2 h to form a SiN / GO toughening phase.

[0049] This embodiment also provides a method for preparing a high wear-resistant tungsten steel alloy, which specifically comprises the following steps:

[0050] S1, weigh 10 parts of anhydrous ethanol, add 1 part of SiN / GO toughening phase, 0.5 parts of V and 1.3 parts of Mo into the anhydrous ethanol and mix well to obtain a mixture, put the mixture into a wet mill for ball milling for 24 hours, and pass through a 400 mesh sieve to obtain a toughening slurry;

[0051] S2, drying the toughened slurry obtained in step S1, pressing and molding to obtain a compact, vacuum sintering the compact in a vacuum tube furnace, raising the sintering temperature from room temperature to 900° C. in a nitrogen atmosphere, and maintaining the temperature at 900° C. for 0.5 h to form a toughened layer;

[0052] S3, weighing 80 parts of acetone, adding 86 parts of WC, 1 part of TiC, 5 parts of Al-B-Sn nano-oxide, 0.2 parts of Mn and 0.5 parts of inhibitor into the acetone to form a mixed slurry, adding 4 parts of a molding agent into the mixed slurry, ball milling, and drying to obtain a powder;

[0053] S4, covering the toughening layer obtained in step S2 with the powder obtained in step S3, pressing into shape, and vacuum sintering. In a nitrogen atmosphere, rapidly raising the temperature from room temperature to 1200°C at a heating rate of 20°C / min, maintaining at this temperature for 0.5h, then raising the temperature from 1200°C to 1400°C at a heating rate of 10°C / min, and maintaining at 1400°C for 0.5h, and obtaining a high wear-resistant tungsten steel alloy after cooling.

[0054] Embodiment 2: This embodiment provides a high wear-resistant tungsten steel alloy, which is composed of the following raw materials in percentage by mass: 89 parts of WC, 1.8 parts of TiC, 3 parts of Al-B-Sn nano-oxide, 1 part of V, 1.6 parts of Mn, 0.8 parts of Mo, 1 part of inhibitor, 5 parts of forming agent, and 2 parts of SiN / GO toughening phase;

[0055] The inhibitor is prepared by mixing VC and Cr3C2, with a mass ratio of 1:0.6;

[0056] The molding agent is polyvinyl alcohol;

[0057] The raw materials for preparing the Al-B-Sn nano-oxide are: Al(NO3)3·9H2O, acetylacetone, SnO2 and H3BO3;

[0058] The preparation method of the Al-B-Sn nano-oxide specifically comprises the following steps:

[0059] (1) Weigh Al(NO3)3·9H2O and dissolve it in ethylene glycol, add acetylacetone, stir at a constant temperature of 60°C for 2 h, add SnO2, the amount ratio of Al(NO3)3·9H2O, SnO2, acetylacetone and ethylene glycol is 1.5 g:0.5 g:5 mL:30 mL, stir and mix to form a mixed solution;

[0060] (2) adding H3BO3 to the mixed solution obtained in step (1), the amount ratio of H3BO3 to the mixed solution being 0.2 g:30 mL, and stirring at a constant temperature for 1 h to obtain a precursor mixed solution;

[0061] (3) The precursor mixed solution was aged for 48 hours to obtain a sol, and then the sol was placed in a muffle furnace for calcination. At room temperature, it was heated from room temperature to 300°C at 3°C / min, and maintained at 300°C for 2 hours. It was cooled to room temperature to obtain Al-B-Sn nano-oxide.

[0062] The raw materials for preparing the SiN / GO toughening phase are: graphite powder, sodium nitrate and potassium permanganate;

[0063] The preparation method of the SiN / GO toughening phase specifically comprises the following steps:

[0064] (a) Add concentrated sulfuric acid to a beaker, slowly add graphite powder, sodium nitrate and potassium permanganate, the amount ratio of graphite powder, sodium nitrate, potassium permanganate and concentrated sulfuric acid is 1g:0.6g:3g:25mL, put it in a water bath at a temperature of 15°C for 3 hours, then stir it at a speed of 300 rpm at 35°C for 60 minutes with a thermostatic stirrer to form a mixed solution;

[0065] (b) adding 30% hydrogen peroxide to the mixed solution obtained in step (a), with the volume ratio of hydrogen peroxide to the mixture being 1:3, reacting until no bubbles are generated in the beaker, then stirring at 200 rpm for 60 min at room temperature, washing with deionized water 5 times, diluting with 0.01 M dilute hydrochloric acid to a pH value of 7, and drying in a vacuum drying oven at 75° C. for 12 h to obtain GO brown powder;

[0066] (c) The GO brown powder prepared in step (b) was dissolved in a THF solution, and SiN was added. The amount ratio of SiN, GO brown powder and THF was 0.8 g:1 g:15 mL. The mixture was stirred evenly at a speed of 180 rpm and calcined, i.e., heated to 500°C at a rate of 12°C / min at room temperature and maintained at 500°C for 3 h to form a SiN / GO toughening phase.

[0067] This embodiment also provides a method for preparing a high wear-resistant tungsten steel alloy, which specifically comprises the following steps:

[0068] S1, weigh 15 parts of anhydrous ethanol, add 2 parts of SiN / GO toughening phase, 1 part of V and 0.8 parts of Mo into the anhydrous ethanol and mix well to obtain a mixture, put the mixture into a wet mill for ball milling for 24 hours, and pass through a 450 mesh sieve to obtain a toughening slurry;

[0069] S2, drying the toughened slurry obtained in step S1, pressing the toughened slurry into a compact, placing the compact in a vacuum tube furnace for vacuum sintering, raising the sintering temperature from room temperature to 1000° C. in a nitrogen atmosphere, and maintaining the temperature at 1000° C. for 0.8 h to obtain a toughened layer;

[0070] S3, weighing 80-100 parts of acetone, adding 89 parts of WC, 1.8 parts of TiC, 3 parts of Al-B-Sn nano oxide, 1.6 parts of Mn and 1 part of inhibitor into the acetone to form a mixed slurry, adding a molding agent to the mixed slurry, ball milling, and drying to obtain a powder;

[0071] S4, covering the toughening layer obtained in step S2 with the powder obtained in step S3, pressing into shape, and vacuum sintering. In a nitrogen atmosphere, rapidly raising the temperature from room temperature to 1200°C at a heating rate of 20°C / min, maintaining at 1200°C for 0.8h, then raising the temperature from 1200°C to 1400°C at a heating rate of 10°C / min, and maintaining at 1400°C for 0.8h, and obtaining a high wear-resistant tungsten steel alloy after cooling.

[0072] Embodiment 3: This embodiment provides a high wear-resistant tungsten steel alloy, which is composed of the following raw materials in parts by weight: 92 parts of WC, 2.5 parts of TiC, 1 part of Al-B-Sn nano-oxide, 1.2 parts of V, 2 parts of Mn, 1 part of Mo, 1.5 parts of inhibitor, 6 parts of forming agent, and 3 parts of SiN / GO toughening phase;

[0073] The inhibitor is prepared by mixing VC and Cr3C2, with a mass ratio of 1:0.6;

[0074] The molding agent is polyvinyl alcohol;

[0075] The raw materials for preparing the Al-B-Sn nano-oxide are: Al(NO3)3·9H2O, acetylacetone, SnO2 and H3BO3;

[0076] The preparation method of the Al-B-Sn nano-oxide specifically comprises the following steps:

[0077] (1) Weigh Al(NO3)3·9H2O and dissolve it in ethylene glycol, add acetylacetone, stir at constant temperature at 60°C for 2 h, add SnO2, the amount ratio of Al(NO3)3·9H2O, SnO2, acetylacetone and ethylene glycol is 2g:0.5g:5mL:30mL, stir and mix to form a mixed solution;

[0078] (2) adding H3BO3 to the mixed solution obtained in step (1), the amount ratio of H3BO3 to the mixed solution being 0.3 g:30 mL, and stirring at a constant temperature for 1 h to obtain a precursor mixed solution;

[0079] (3) The precursor mixed solution was aged for 48 hours to obtain a sol, and then the sol was placed in a muffle furnace for calcination. At room temperature, it was heated from room temperature to 300°C at 3°C / min, and maintained at 300°C for 2 hours. It was cooled to room temperature to obtain Al-B-Sn nano-oxide.

[0080] The raw materials for preparing the SiN / GO toughening phase are: graphite powder, sodium nitrate and potassium permanganate;

[0081] The preparation method of the SiN / GO toughening phase specifically comprises the following steps:

[0082] (a) Add concentrated sulfuric acid to a beaker, slowly add graphite powder, sodium nitrate and potassium permanganate, the amount ratio of graphite powder, sodium nitrate, potassium permanganate and concentrated sulfuric acid is 1g:0.6g:3g:25mL, put it in a water bath at a temperature of 15°C for 3 hours, and then stir it at 35°C for 60 minutes with a thermostatic stirrer to form a mixed solution;

[0083] (b) adding 30% hydrogen peroxide to the mixed solution obtained in step (a), with the volume ratio of hydrogen peroxide to the mixture being 1:3, reacting until no bubbles are generated in the beaker, then stirring at 200 rpm for 60 min at room temperature, washing with deionized water 5 times, diluting with 0.01 M dilute hydrochloric acid to a pH value of 7, and drying in a vacuum drying oven at 75° C. for 12 h to obtain GO brown powder;

[0084] (c) The GO brown powder prepared in step (b) was dissolved in a THF solution, and SiN was added in a ratio of 1 g:1 g:15 mL of SiN:GO brown powder to THF. The mixture was stirred evenly at a speed of 180 rpm and calcined, i.e., heated to 600°C at a rate of 12°C / min at room temperature and maintained at 600°C for 4 h to form a SiN / GO toughening phase.

[0085] This embodiment also provides a method for preparing a high wear-resistant tungsten steel alloy, which specifically comprises the following steps:

[0086] S1, weigh 20 parts of anhydrous ethanol, add 3 parts of SiN / GO toughening phase, 1.2 parts of V, and 1 part of Mo into the anhydrous ethanol and mix well to obtain a mixture, put the mixture into a wet grinder for ball milling for 24 hours, and pass through a 500-mesh sieve to obtain a toughening slurry;

[0087] S2, drying the toughened slurry obtained in step S1, pressing the toughened slurry into a compact, and placing the compact into a vacuum tube furnace for sintering, raising the sintering temperature from room temperature to 1100° C. in a nitrogen atmosphere, and maintaining the temperature at 1100° C. for 1 hour to obtain a toughened layer;

[0088] S3, weighing 100 parts of acetone, adding 92 parts of WC, 2.5 parts of TiC, 1 part of Al-B-Sn nano oxide, 2 parts of Mn and 1.5 parts of inhibitor into the acetone to form a mixed slurry, adding a molding agent to the mixed slurry, ball milling, and drying to obtain a powder;

[0089] S4, covering the toughening layer obtained in step S2 with the powder obtained in step S3, pressing into shape, and performing vacuum sintering. In a nitrogen atmosphere, rapidly raising the temperature from room temperature to 1200°C at a heating rate of 20°C / min, maintaining at 1200°C for 1 hour, then raising the temperature from 1200°C to 1400°C at a heating rate of 10°C / min, and maintaining at 1400°C for 1 hour, and obtaining a high wear-resistant tungsten steel alloy after cooling.

[0090] The difference between Comparative Example 1 and Example 1 is that the addition of Al-B-Sn nano-oxide is eliminated, and the rest is the same as Example 1.

[0091] The difference between Comparative Example 2 and Example 1 is that the addition of SiN / GO toughening phase is eliminated, and the rest is the same as Example 1.

[0092] The difference between Comparative Example 3 and Example 1 is that the preparation method of the high wear-resistant tungsten steel alloy is as follows: weigh SiN / GO toughening phase and V and Mo by weight, mix them evenly in anhydrous ethanol to obtain a mixture, put the mixture into a wet grinder for ball milling for 24 hours, and pass through a 400-500 mesh sieve to obtain a toughening slurry; WC, TiC, Al-B-Sn nanooxide, Mn, and inhibitor are mixed by weight, added to the toughening slurry and mixed evenly, acetone is added to form a mixed slurry, a molding agent is added to the mixed slurry, ball milling is performed, and powder is obtained by drying; the powder is pressed into shape and vacuum sintered. In a nitrogen atmosphere, the temperature is rapidly increased from room temperature to 1200°C at a heating rate of 20°C / min, maintained at 1200°C for 0.5-1h, then increased from 1200°C to 1400°C at a heating rate of 10°C / min, and maintained at 1400°C for 0.5-1h, and a high wear-resistant tungsten steel alloy is obtained after cooling.

[0093] Experimental Example 1: According to GB / T 230.3-2022 "Rockwell Hardness Test for Metallic Materials", the hardness of the high wear-resistant tungsten steel alloy prepared by the present invention was tested. The tungsten steel alloys prepared in Example 1-3 and Comparative Example 3 were used as samples. The Rockwell hardness was tested using a D-150 Rockwell hardness tester. After being made into a standard sample by wire cutting, the sample was placed on a sample table for dotting. Five points were selected for each sample, and the average value was finally calculated. The calculated results are recorded in Table 1.

[0094] Experimental Example 2: A rubber wheel wear testing machine (MLG-130) was used to conduct an abrasive wear test on the sample. The high wear-resistant tungsten steel alloy prepared in Examples 1-3 and Comparative Examples 1-3 was used as a wear sample, and the size of the wear sample was 57mm×25.5mm×6mm. Quartz sand of 212-270μm was used as an abrasive. During the experiment, the flow rate of the abrasive was 300g / min, the speed of the rubber wheel was 200r / min, and the wear load was 130N. In order to ensure the accuracy of the wear results, the sample was pre-grinded for 10 minutes before the formal wear to reduce the experimental error. After the formal wear was completed, the worn sample was rinsed with alcohol and cleaned with ultrasonic oscillation for 10 minutes to remove the abrasive debris on the wear surface. It was then weighed with an electronic balance. The wear mass loss was calculated by the mass difference of the sample before and after wear. The total wear time was 120 minutes, and the wear weight loss was measured every 30 minutes. The wear weight loss results are as follows: Figure 2 shown.

[0095] Experimental Example 3: According to JB / T 12616-2016 "Test Method for Fracture Toughness of Cemented Carbide Tool Matrix Material", the fracture toughness of the tungsten steel alloy prepared by the present invention was tested. The thickness of the sample surface was ground off to 0.2 mm. During the preparation of the sample, the influence of heat, cold working, etc. on the surface hardness of the sample should be avoided. The test surface of the sample and the corresponding support surface should be parallel planes to each other. The sample is fixed on the fracture toughness testing machine to ensure that the crack tip is located below the loading point. The sample is loaded at a speed of 0.1 mm / min. During the loading process, the load and crack tip displacement or sample bending deflection are continuously recorded. When the load reaches the maximum value or begins to decrease, the loading is stopped, and the fracture toughness is calculated based on the recorded data. The results are recorded in Table 1.

[0096] Table 1

[0097]

[0098] Experimental Example 4: According to YB / T 5349-2014 "Metallic Material Bending Mechanical Properties Test Method", the bending strength was tested. The wear-resistant tungsten steel alloy prepared in Examples 1-3 and Comparative Examples 1-3 was used as a sample, and a rectangular strip of 15×10×180 mm was prepared. The MTS-809 electro-hydraulic servo universal testing machine was used. Before the test, the width and height of each sample were measured and recorded, and then the three-point bending test device was installed and the span was adjusted. The sample was placed on two supporting rollers stably and symmetrically, and the test was started. The sample was continuously loaded at a stress rate of 5 MPa / s until it broke, and the bending strength was calculated. The results are recorded in Table 1.

[0099] The results in Table 1 show that the hardness of the high wear-resistant tungsten steel alloy prepared by the present invention is higher than that of the comparative examples 1-3, indicating that the high wear-resistant tungsten steel alloy prepared by the present invention has high hardness, and the fracture toughness results show that the high wear-resistant tungsten steel alloy prepared by the present invention reaches 16.2 MPa·m 1 / 2 , indicating that the added toughening layer plays a good role, making the prepared high wear-resistant tungsten steel alloy have high fracture toughness. The bending strength results further show that the high wear-resistant tungsten steel alloy prepared by the present invention has excellent wear resistance and high temperature oxidation resistance, good toughness, strength and bending resistance.

[0100] Figure 1 The results show that the prepared high wear-resistant tungsten steel alloy has a uniform microstructure with a grain size of about 200nm. Figure 2 It can be seen that the average grain size of the high wear-resistant tungsten steel alloy prepared by the present invention is less than 0.5 μm, and has ultrafine grains, which indicates that the nano-oxide and inhibitor added in the present invention play a good role, and a dense tungsten steel alloy with fine grains is obtained, thereby enhancing the wear resistance of the tungsten steel alloy. Figure 3 The results show that the wear weight loss of the high wear-resistant tungsten steel alloy prepared by the present invention is significantly lower than that of the control example, indicating that the high wear-resistant tungsten steel alloy prepared by the present invention has excellent wear resistance.

[0101] In summary, through the verification of experimental examples and comparative examples, it can be known that the addition of Al-B-Sn nano-oxide helps to refine the grains of tungsten steel alloy, making the organizational structure more fine and uniform. This uniform and fine organizational structure not only improves the mechanical properties of the material, but also enhances its thermal stability and corrosion resistance. SiN / GO toughening phase is added. The introduction of this toughening phase significantly improves the fracture toughness of tungsten steel alloy. When subjected to impact or vibration loads, the alloy shows better resistance to crack propagation, thereby improving the reliability and service life of the material. Through the design of toughening phase and hard phase, the present invention achieves a good balance of hardness, wear resistance, density and fracture toughness. This comprehensive performance improvement enables tungsten steel alloy to show excellent performance in a variety of application scenarios, including but not limited to cutting tools, mold manufacturing, wear-resistant parts and other fields, and has broad application prospects.

[0102] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A high wear-resistant tungsten steel alloy, characterized in that: The high wear-resistant tungsten steel alloy is composed of the following raw materials in parts by weight: 86-92 parts of WC, 1-2.5 parts of TiC, 1-5 parts of Al-B-Sn nano-oxide, 0.5-1.2 parts of V, 1.2-2 parts of Mn, 0.2-1 parts of Mo, 0.5-1.5 parts of inhibitor, 4-6 parts of forming agent, and 1-3 parts of SiN / GO toughening phase; The inhibitor is prepared by mixing VC and Cr3C2, with a mass ratio of 1:0.6; The molding agent is polyvinyl alcohol; The raw materials for preparing the Al-B-Sn nano-oxide are: Al(NO3)3·9H2O, acetylacetone, SnO2 and H3BO3; The preparation method of the Al-B-Sn nano-oxide specifically comprises the following steps: (1) Weigh Al(NO3)3·9H2O and dissolve it in ethylene glycol, add acetylacetone, stir at constant temperature, add SnO2, stir and mix to form a mixed solution; (2) adding H3BO3 to the mixed solution obtained in step (1), stirring at a constant temperature, to obtain a precursor mixed solution; (3) aging the precursor mixed solution to obtain a sol, then calcining it, and cooling it to room temperature to obtain an Al-B-Sn nano-oxide.

2. A high wear-resistant tungsten steel alloy according to claim 1, characterized in that: In step (1), the usage ratio of Al(NO3)3·9H2O, SnO2, acetylacetone and ethylene glycol is 1-2g:0.5g:5mL:30mL.

3. The high wear-resistant tungsten steel alloy according to claim 1, characterized in that: In step (2), the usage ratio of H3BO3 to the mixed solution is 0.1-0.3 g:30 mL.

4. The high wear-resistant tungsten steel alloy according to claim 1, characterized in that: The raw materials for preparing the SiN / GO toughening phase are: graphite powder, sodium nitrate and potassium permanganate; The preparation method of the SiN / GO toughening phase specifically comprises the following steps: (a) slowly adding graphite powder, sodium nitrate and potassium permanganate into concentrated sulfuric acid, placing the mixture in a water bath, and stirring at a constant temperature to form a mixed solution; (b) adding 30% hydrogen peroxide to the mixed solution obtained in step (a), reacting until no bubbles are generated, stirring at room temperature, washing with deionized water, and then diluting and washing with 0.01M dilute hydrochloric acid to a pH value of 7, and drying to obtain GO brown powder; (c) The GO brown powder prepared in step (b) is dissolved in THF, SiN is added, stirred evenly, and calcined to form a SiN / GO toughening phase.

5. The high wear-resistant tungsten steel alloy according to claim 1, characterized in that: In step (a), the amount ratio of the graphite powder, sodium nitrate, potassium permanganate and concentrated sulfuric acid is 1g:0.6g:3g:25mL, in step (b), the volume ratio of the hydrogen peroxide to the mixed solution is 1:3, and in step (c), the amount ratio of the SiN, GO brown powder to THF is 0.5-1g:1g:15mL.

6. A method for preparing a high wear-resistant tungsten steel alloy according to any one of claims 1 to 5, characterized in that: The specific steps include: S1, weighing 10-20 parts of anhydrous ethanol, adding SiN / GO toughening phase, V and Mo by weight into the anhydrous ethanol and mixing evenly to obtain a mixture, placing the mixture into a wet mill for ball milling for 24 hours, and passing through a 400-500 mesh sieve to form a toughening slurry; S2, drying the toughening slurry obtained in step S1, pressing and molding to obtain a compact, and vacuum sintering the compact to obtain a toughening layer; S3, weighing 80-100 parts of acetone, adding WC, TiC, Al-B-Sn nano-oxide, Mn and inhibitor into the acetone according to weight parts to form a mixed slurry, adding a molding agent to the mixed slurry, ball milling, and drying to obtain a powder; S4, covering the toughening layer obtained in step S2 with the powder obtained in step S3, pressing and forming, vacuum sintering, and cooling to obtain a high wear-resistant tungsten steel alloy.

7. The method for preparing the high wear-resistant tungsten steel alloy according to claim 6, characterized in that: In step S2, the vacuum sintering is performed in a nitrogen atmosphere by raising the sintering temperature from room temperature to 900-1100°C and maintaining the temperature at 900-1100°C for 0.5-1h.

8. The method for preparing the high wear-resistant tungsten steel alloy according to claim 6, characterized in that: In step S4, the vacuum sintering is carried out in a nitrogen atmosphere by rapidly raising the temperature from room temperature to 1200°C at a heating rate of 20°C / min, maintaining at 1200°C for 0.5-1h, then raising the temperature from 1200°C to 1400°C at a heating rate of 10°C / min, and maintaining at 1400°C for 0.5-1h.

Citation Information

Patent Citations

  • Hard alloy raw material, mining tool hard alloy and preparation method of mining tool hard alloy

    CN103014471A

  • Nanometer hard alloy numerical control cutter material and preparation method thereof

    CN118291802A

  • USE OF Ti and Nb CEMENTED IN TiC IN PROSTHETIC JOINTS

    US20100198353A1

  • Ti(C,N)-BASED CERMET WITH Ni3Al AND Ni AS BINDER AND PREPARATION METHOD THEREOF

    US20150252455A1

  • Cemented carbide comprising carbon nanomaterial and method for producing same

    WO2024225774A1